The Concept of Moral Education Values in the Story of Prophet Ibrahim in Qur’an Surah Ash-Shaffat Verses 99–111: A Study of Tafsir Al-Misbah in the Context of Character Formation - Alfina Ramadhani; Abdul Ghofur; Muhammad Soleh Hasan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study explores the moral education values embedded in the story of Prophet Ibrahim (Abraham), focusing on M. Quraish Shihab’s interpretation in Tafsir Al- Misbah of Surah Ash-Shaffat verses 99–111. The research aims to examine how M. Quraish Shihab interprets and explains the moral values within the story, as well as to analyze their relevance to character formation and moral education for individuals and society. The findings indicate that, according to M. Quraish Shihab’s perspective, the story of Prophet Ibrahim encompasses several moral values, including patience, steadfastness, trust in God, and sincerity. These values form an essential foundation for moral education and provide guidance for individuals in confronting life’s trials and challenges.